2008
DOI: 10.1590/s1516-44462008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of physical fighting among school-going adolescents in Santiago, Chile

Abstract: [OR = 3.89, 95% CI (3.11, 4.85)]. Substance use (cigarette smoking, drinking alcohol, and using drugs) and bullying victimization were positively associated with fighting [OR = 3.05, 95% CI (2.40, 3.87) [OR = 3.89, 95% CI (3.11, 4.85)]. El uso de substancias (fumar cigarros, beber alcohol y usar drogas) e intimidaciones violentas estuvieron positivamente asociados con agresión [OR = 3.05, 95% CI (2.40, 3.87)] La supervisión parental estuvo asociada negativamente con agresión física [OR = 0.62, 95% CI (0.50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
33
2
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 45 publications
16
33
2
10
Order By: Relevance
“…The current study identified a slight but statistically significant positive association between parental supervision and physical fighting among school students, which contradicts most of the available literature on this issue that identified parental supervision as a protective factor against physical fighting [9, 18, 21, 22]. Furthermore, this finding is more pronounced among male respondents (OR = 1.60, 95% CI (1.43, 1.80)).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current study identified a slight but statistically significant positive association between parental supervision and physical fighting among school students, which contradicts most of the available literature on this issue that identified parental supervision as a protective factor against physical fighting [9, 18, 21, 22]. Furthermore, this finding is more pronounced among male respondents (OR = 1.60, 95% CI (1.43, 1.80)).…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in concordance with those reported by Muula et al on bullying and fighting among Venezuelan adolescents, where a significant dose-response relationship coupled bullying with physical fighting [21]. Likewise, a study by Rudatsikira et al among Chilean adolescents revealed that substance use (cigarette smoking, drinking alcohol, drugs) and being bullied were positively associated with physical fighting [22]. Consequently, bullying and drug abuse interact in a larger vicious cycle and may lead to cognitive and non-cognitive harm such as depression, stress, lack of satisfaction with life, and academic impairment [23].…”
Section: Discussionsupporting
confidence: 91%
“…Most studies are based on samples from Europe and North America. Three studies (i.e., Brown et al, 2008;Rudatsikira, Muula, & Siziya, 2008;Siziya et al, 2013) examined populations from low-income countries in Latin America or Africa. Seventy seven per cent of the studies were retrieved from peerreviewed journal articles.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Second, there are wide-spread public health concerns over heightened levels of youth externalizing behaviors. A recent study of adolescents in Santiago, Chile reported levels of externalizing behaviors, such as bullying (45%), physical fights (41%), drugs (11%), alcohol (33%), cigarettes (30%), to be equivalent to those of youth in Europe and North America (Rudatsikira, Muula, & Siziya, 2008). Therefore, given the high prevalence of parental use of corporal punishment as well as youth externalizing behavior in Chile, a study that examines the link between these two domains of concern may be valuable.…”
mentioning
confidence: 99%